Saturated output-feedback control and state estimation of a class of exothermic tubular reactors. (April 2022) - Franco-de los Reyes, Hugo A.; Alvarez, Jesus
Abstract: The problem of robustly stabilizing and estimating the state of an open-loop unstable continuous exothermic tubular reactor with constrained control is solved with a comprehensive methodology that includes: (i) a control–estimation (CE) system made by a saturated proportional–integral temperature control with anti-windup protector, and a low-order noninterfering (computationally efficient) nonlinear (NL) geometric state estimator, and (ii) closed-loop robust functioning conditions coupled with sensor location, control limits and gain selection criteria. The CE system is obtained as a simplified-robustified realization of the implementation with a robust NL estimator of a constrained NL state-feedback passive or model-predictive robust stabilizing control. The design methodology is illustrated and tested with a representative example through numerical simulation. Highlights: Control–estimation (CE) system design for exothermic tubular reactors. Robust stability conditions with sensor location, control limit and gain selection criteria. Solvability in terms of passivity, detectability, and bifurcation. CE system: PI control with antiwindup protection plus noninterfering state estimator. Estimator built with efficient PDE-to-ODE discretization.